Acute transfusion-related abdominal injury in trauma patients: a case report. (December 2016) - Michel, P.; Wähnert, D.; Freistühler, M.; Laukoetter, M.; Rehberg, S.; Raschke, M.; Garcia, P.
Abstract Background Secondary abdominal compartment syndrome is well known as a life-threatening complication in critically ill patients in an intensive care unit. Massive crystalloid fluid resuscitation has been identified as the most important risk factor. The time interval from hospital admittance to the development of manifest abdominal compartment syndrome is usually greater than 24 hours. In the absence of any direct abdominal trauma, we observed a rapidly evolving secondary abdominal compartment syndrome shortly after hospital admittance associated with massive transfusion of blood products and only moderate crystalloid resuscitation. Case presentation We report the case of an acute secondary abdominal compartment syndrome developing within 3 to 4 hours in a 74-year-old polytraumatized white woman. Although multiple fractures of her extremities and a B-type pelvic ring fracture were diagnosed by a full body computed tomography scan, no intra-abdominal injury could be detected. Hemorrhagic shock with a drop in her hemoglobin level to 5.7 g/dl was treated by massive transfusion of blood products and high doses of catecholamines. Shortly afterwards, her pulmonary gas exchange progressively deteriorated and mechanical ventilation became almost impossible with peak airway pressures of up to 60 cmH2 O. Her abdomen appeared rigid and tense accompanied by a progressive hemodynamic decompensation necessitating mechanic cardiopulmonary resuscitation. Although preoperative computed tomography scans showed no signs of intra-abdominal fluid, a decompressive laparotomy under cardiopulmonary resuscitation conditions was performed and 2 liters of ascites-like fluid disgorged. Her hemodynamics and pulmonary ventilation improved immediately. Conclusions This case report describes for the first time acute secondary abdominal compartment syndrome in a trauma patient, evolving in a very short time period. We hypothesize that the massive transfusion of blood products along with high doses of catecholamines triggered the acute development of abdominal compartment syndrome. Trauma teams need to consider a rapidly developing secondary abdominal compartment syndrome to be a potential cause of hemodynamic decompensation not only in the later phase of treatment but also in the emergency phase of treatment.